A Prophetic Law Basis for Strengthening the Values of Indonesian Consumer Protection Law Culture - Musataklima; Adi Sulistiyono; M. Syamsudin (Prophetic Law Review, 2024)
This study analyzes the factors that cause the weakness of consumer empowerment in Indonesia and conducts a comparison to the other countries in order to strengthen the values of Consumer Protection Law based on the Prophetic Law. This study combines the normative and empirical legal research. The qualitative data used are from primary and secondary sources. The primary data are obtained through interviews with predetermined informants. Secondary data are collected through literature research. The results show that the lack of consumer empowerment is caused by the long distance between the institution implementing consumer protection and the consumer itself. As a result, it is difficult for consumers to access. On the other hand, the methods used to protect consumers are still non-formal. Second, strengthening the values of consumer protection law culture can be done through formal education based on Islamic prophetic values because with such a design, the intensity of consumer education can run in a programmed, organized, and systematic manner, and prophetic values can become the basis of energy to always fight for consumer rights through a critical attitude.